Distinct Autism Spectrum Disorder Phenotype and Hand-Flapping Stereotypes: Two Siblings with Novel Homozygous Mutation in TRAPPC9 Gene and Literature Review - Bolat, Hilmi; Uensel-Bolat, Gul; Derin, Hatice; Sen, Askin; Ceylaner, Serdar (Karger, 2022)
Objective: Pathogenic mutations of the TRAPPC9 gene are the rare genetic causes of autosomal recessive intellectual disability (ID). There are several features that are not fully penetrant such as microcephaly, dysmorphic facial features, obesity, autism spectrum disorder (ASD), attention-deficit hyperactivity disorder (ADHD), and brain abnormalities in TRAPPC9 mutations. Methods: We performed whole-exome sequencing to evaluate 2 Turkish siblings with ASD and ID born to healthy and consanguineous parents. Parental samples were also analyzed, specifically targeting variants detected in these patients. Results: We present a novel homozygous mutation in the TRAPPC9 gene, c.484G>T (p.Glu162Ter). Additionally, we aim to provide a more comprehensive understanding of the clinical features of a novel homozygous TRAPPC9 mutation. In addition to ID, the siblings in this report suffered from ASD and specific stereotypes as hand-flapping behavior. Conclusion: Although there are inconsistencies in the presentation of ASD in TRAPPC9 mutations, repetitive behaviors (hand-flapping ) were typical in our cases and several previous reports. The current mutation was described to cause a homozygous premature termination codon that resulted in the absence of the TRAPPC9 protein. We suggest that TRAPPC9 mutations are not only related to ID but also to ASD and hand-flapping behaviors.
Keywords: Autism spectrum disorder; Intellectual disability; MRT13 TRAPPC9